Which food literacy dimensions are associated with diet quality among Canadian parents?. Issue 8 (26th June 2019) - Fernandez, Melissa Anne; Desroches, Sophie; Marquis, Marie; Lebel, Alexandre; Turcotte, Mylène; Provencher, Véronique
Abstract : Purpose: The purpose of this paper is to explore associations between different food literacy dimensions and diet quality among a sample of Canadian parents and examine differences in the prevalence of food literacy items between mothers and fathers. Design/methodology/approach: Parents responsible for food preparation ( n =767) completed an online survey including dietary intakes and 22 items across five dimensions of food literacy (knowledge, planning, cooking, food conceptualisation and social aspects). Differences between genders for each item were analysed with χ 2 tests. The healthy eating index (HEI) adapted to the Canadian Food Guide (CFG) was computed from a food frequency questionnaire. Associations between HEI scores and each item were analysed with linear regression models, controlling for sociodemographic variables and multiple testing. Findings: Of parents responsible for food preparation, 81 per cent were mothers. The mean HEI score was 76.6 (SD: 10.6) and mothers reported healthier diets in comparison to fathers ( p =0.01). More mothers than fathers used CFG recommendations, selected foods based on nutrition labels, made soups, stews, muffins and cakes from scratch and added fruits and vegetables to recipes ( p <0.05). More fathers reduced the salt content of recipes than mothers ( p =0.03). Two knowledge items and seven food conceptualisation items were significantly associated with better HEI, after controlling for covariates and multiple testing. Planning items, cooking skills and social aspects were not significantly associated with HEI. Originality/value: This study investigates multiple dimensions of food literacy and identifies knowledge and food conceptualisation as potential targets for future interventions involving parents responsible for household meal preparation. This study highlights the importance of considering gender differences in food literacy.